ANALISIS KEDUDUKAN DAN PERAN AUDITOR INTERNAL PADA PERUSAHAAN KSO PERTAMINA EP-SAMUDRA ENERGY BWP MERUAP DI KELURAHAN SAROLANGUN KEMBANG - Asmo, Abdi; Majid, M. Nazori (Manajemen Keuangan Syariah, 2022)
This research is entitled "Analysis of the Position and Role of Internal Auditors at Kso Pertamina Ep - Samudra Energy Bwp Company Overflowing in Sarolangun Kembang Village, Sarolangun District". The purpose of this study is to analyze the position of the internal auditor at KSO Pertamina EP – Samudra Energy BWP Meruap and to analyze the role of internal auditors at KSO Pertamina EP – Samudra Energy BWP Meruap.The research method used is descriptive qualitative method with hemeutic analysis techniques, phenomology and historical analysis. The results showed that the position of the Internal Audit Field is under the Finance Supervisor. This is because according to the results of the research, this was carried out at the Pertamina EP – Samudera Energy BWP KSO Field office. Most of the activities that are considered to be seriously handled are in the financial sector which is considered very sensitive. Besides that, it does not mean that in terms of mining operations, inspections are carried out through the inspection division of the Jakarta head office which is carried out for 3 years 1 time. The role of the Internal Audit Field in terms of audit reports of financial statements. The Internal Audit Field audits financial statements in the accounting field with the output in the form of notes on financial statements guided by the Internal Audit Field code of ethics that has been determined by the field of examination from the Jakarta head office. In addition, in terms of compliance audits and operational audits, the Internal Audit Field is not authorized to audit in terms of managerial compliance because the position of the Internal Audit Field is only under the Finance Supervisor who is principally responsible for the annual financial statements. Meanwhile, in terms of mining operations, the Internal Audit Field does not play a full role by only reporting in the form of invoices that are inputted in a special application that will be connected to the inspection division of the Jakarta head office.